Re‐evaluation of acetic acid, lactic acid, citric acid, tartaric acid, mono‐ and diacetyltartaric acid, mixed acetic and tartaric acid esters of mono‐ and diglycerides of fatty acids (E 472a‐f) as food additives - EFSA Panel on Food Additives and Flavourings (FAF); Maged Younes; Gabriele Aquilina; Laurence Castle; Karl‐Heinz Engel; Paul Fowler; Maria Jose Frutos Fernandez; Peter Fürst; Rainer Gürtler; Ursula Gundert‐Remy; Trine Husøy; Wim Mennes; et al. (EFSA Journal, 2020)
Abstract The Panel on Food Additives and Flavourings (FAF) provided a scientific opinion re‐evaluating the safety of acetic acid, lactic acid, citric acid, tartaric acid, mono‐ and diacetyltartaric acids, mixed acetic and tartaric acid esters of mono‐ and diglycerides of fatty acids (E 472a‐f) as food additives. All substances had been previously evaluated by the Scientific Committee for Food (SCF) and by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). Hydrolysis of E472a,b,c,e was demonstrated in various experimental systems, although the available data on absorption, distribution, metabolism, excretion (ADME) were limited. The Panel assumed that E472a‐f are extensively hydrolysed in the GI tract and/or (pre‐)systemically after absorption into their individual hydrolysis products which are all normal dietary constituents and are metabolised or excreted intact. No adverse effects relevant for humans have been identified from the toxicological database available for E472a‐f. The Panel considered that there is no need for a numerical acceptable daily intake (ADI) for E 472a,b,c. The Panel also considered that only l(+)‐tartaric acid has to be used in the manufacturing process of E472d,e,f. The Panel established ADIs for E 472d,e,f based on the group ADI of 240 mg/kg body weight (bw) per day, expressed as tartaric acid, for l(+)‐tartaric acid‐tartrates (E334‐337, 354) and considering the total amount of l(+)‐tartaric acid in each food additive. Exposure estimates were calculated for all food additives individually, except for E 472e and f, using maximum level, refined exposure and food supplements consumers only scenarios. Considering the exposure estimates, there is no safety concern at their reported uses and use levels. In addition, exposure to tartaric acid released from the use of E 472d,e,f was calculated. The Panel also proposed a number of recommendations.